You need to define h(x) to find its inverse.
The general answer is to replace h(x)= with y=. Then you make x the subject of the equation so that you get x= some function of y. That function is the inverse of the original function.
Example: h(x)=2x+5. Write y=2x+5. Now solve for x: x=(y-5)/2 so h⁻¹(y)=(y-5)/2 and h⁻¹(x)=(x-5)/2 is the inverse of h(x).
Hey there!
$8.8
$26,460
Hope it helps... Have a great day!
Answer:
50°
Step-by-step explanation:
x+15+2x=90
3x=90-15=75
x=75/3=25
one acute angle=25+15=40°
other acute angle=2×25=50°
Answer:
(f+g)(x) = 13x + 3
Step-by-step explanation:
Rewrite f(x)=2x+7 and g(x)=11x-4 in columns, as follows:
f(x)=2x+7
+g(x)=11x-4
----------------
Now add each column separately.
f(x)+g(x) = (f+g)(x) ("the sum of functions f and g")
2x + 11x = 13x, and, finally, 7-4 = 3.
Therefore,
f(x)=2x+7
+g(x)=11x-4
----------------
(f+g)(x) = 13x + 3